Effects of obesity on functional capacity. (13th August 2013) - Pataky, Zoltan; Armand, Stéphane; Müller‐Pinget, Solange; Golay, Alain; Allet, Lara
<x xml:space="preserve">Abstract</x> Objective To assess the relationships between BMI and walking speed, balance control, sit‐to‐stand performance (a measure of mass specific lower limb power), and endurance. Design and Methods Thirty‐six women with a BMI ≥ 30 kg/m2 and 10 women with normal body weight (BMI between 18 kg/m2 and 25 kg/m2) were enrolled in this observational study. The obese group comprised 12 persons with a BMI ≥ 30 and <35 (obese), 14 subjects with a BMI ≥ 35 and <40 (severe obesity) and 10 people with a BMI ≥ 40 kg/m2 (morbid obesity). All subjects underwent a clinical examination, a gait test, an endurance test (6 minutes walking test), a mass specific lower limb power test (five times sit‐to‐stand) and a balance test. Results Obese women exhibited slower fast gait speeds (P < 0.05) with correspondingly shorter stride lengths, poorer sit‐to‐stand performance (P < 0.05), and endurance (P < 0.05). However, once the state of severe obesity was reached, additional weight gain (morbid obesity) does not seem to decrease these functional capacities any further. Conclusion This study underlines the importance of assessing obese patients' related physical problems in an early stage of obesity in order to focus exercise regimens and promote appropriate health behaviors.